ไพโรไลซิสของจุลสาหร่ายเพื่อผลิตเชื้อเพลิงเหลวในเครื่องปฏิกรณ์แบบต่อเนื่อง - ศรัณร์พงศ์ คำศรีสุขต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This research aims to study the parameters which are affected to the pyrolysis liquid yield and product distribution from the pyrolysis of micro algae. The experiments of pyrolysis of micro algae were carried out in continuous reactor to investigate the effects of pyrolysis parameters. The pyrolysis temperature, feed rate, nitrogen flow rate and particle size were varied in the ranges of 400 to 600 ° C, 0.41 to 3.30 kilogram per hour, 50 to 250 milliliter per minute and less than 0.15 to more than 0.84 millimeter, respectively. The maximum liquid yield of 42.54% was obtained at the pyrolysis temperature at 500 °C, feed rate of 0.61 kilogram per hour, nitrogen flow rate of 200 milliliter per minute and the particle size of micro algae of 0.25-0.50 millimeter. The chemical composition of liquid products were analyzed by gas chromatography mass spectrometry and simulated distillation gas chromatography. The result shown that bio-oil composed derivatives of amide, carbonyl and phenol. The bio-oil component was obtained as the range from diesel to long residue which are containing carbon atoms more than 15 atoms. The physical chemical analysis also showed that bio-oil from micro algae could be a source of renewable fuel.